2022
DOI: 10.3389/fmicb.2022.846468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plantation Type and Soil Depth on Microbial Community Structure and Nutrient Cycling Function

Abstract: Declining soil quality and microecological imbalances were evaluated in larch plantations in this study. One potential solution to this problem is the cultivation of mixed coniferous and broad-leaved plantations. However, it is unclear whether and how soil microbial community structure and nutrient cycling function would be affected by mixed plantations and soil depths. In this study, we used high-throughput sequencing technology to investigate bacterial 16S and fungal ITS regions for comparisons of soil micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…The significant positive correlation with available P and Gaiellaceae abundance found in this study has been reported by other researchers in different soils and is attributed to genera in this family having the ability to produce alkaline and acid phosphatase (Wang et al, 2022b). Solibacteraceae are known to proliferate in low P conditions (Lang et al, 2021;Oliverio et al, 2020) and the negative correlation between available P and Solibacteraceae found in this study supports this.…”
Section: Discussionsupporting
confidence: 91%
“…The significant positive correlation with available P and Gaiellaceae abundance found in this study has been reported by other researchers in different soils and is attributed to genera in this family having the ability to produce alkaline and acid phosphatase (Wang et al, 2022b). Solibacteraceae are known to proliferate in low P conditions (Lang et al, 2021;Oliverio et al, 2020) and the negative correlation between available P and Solibacteraceae found in this study supports this.…”
Section: Discussionsupporting
confidence: 91%
“…Hyphomicrobiaceae, Bradyrhizobiaceae and Acetobacteraceae, which are known to cope with nitrogen starvation, were observed in both vegetation zones as well as Gaiellaceae and Sphingomonadaceae, bacteria associated with phosphorous limitations or metal pollution, respectively. (72,73). Thus, although a certain level of divergence was noticed in the chemical rhizosphere markers between plant species, similar ecological consequences on the soil microbiome were found.…”
Section: Discussionmentioning
confidence: 99%
“…The Spearman’s correlation heatmaps between bacterial and fungal groups were constructed via R software (Version 3.3.1) pheatmap package [ 27 ]. The Kruskal-Wallis H test was used to analyze the difference of functional bacterial community categories among different samples [ 28 ]. Distance-based redundancy analysis (db-RDA) was performed using the vegan package in R software to investigate the relationships among microbial composition, enzyme activity, and silage chemical components content [ 29 ].…”
Section: Methodsmentioning
confidence: 99%